Investigando a aprendizagem da resolução de problemas combinatórios em licenciandos em matemática - ROCHA, José de Arimatéa (2006)
In this work, we study the learning of the resolution of combinatories problems for students of 4th period of the Course of Mathematics of the Universidade Federal Rural de Pernambuco. Our research was developed in two stages: In the first stage we investigate this learning when the pupils were submitted to a traditional education practice. In the second stage we use the Kelly Experience’s Cycle to organize action that the pupils were leading so that they planned education and they presented a lesson on Combinatories, acting as if teachers were. We evidence that in general the students have difficulties in the resolution of combinatories problems constructing little practical learning during the traditional practice. The results also show that the use of the kellyan cycle incorporates possibilities of practical that induce the reflective reasoning on the pupils and their interactive behavior. Yet, when leading the pupils to be acted as if teachers were elaborating a plan of theaching and a lesson on Combinatories, the CEK provided that they incorporated in significant way to the learning of resolution of combinatories problems.